2010
DOI: 10.1111/j.1365-2362.2010.02278.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of adipokine production in human adipose tissue by propionic acid

Abstract: We demonstrate that PA stimulates expression of the anorexigenic hormone leptin and reduces the pro-inflammatory factor resistin in human adipose tissue depots. This suggests that PA is involved in regulation of human energy metabolism and inflammation and in this way may influence the development of obesity and type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
154
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(161 citation statements)
references
References 40 publications
6
154
0
1
Order By: Relevance
“…In 2004, Xiong et al [147] reported increased plasma leptin levels in mice following acute oral administration of sodium propionate. Enhanced expression of this anorexigenic hormone in human adipose tissue was also reported by Al-Lahham et al [148] in 2010. Both studies suggest an involvement of GPR41 in this process.…”
Section: Propionic Acidsupporting
confidence: 70%
See 1 more Smart Citation
“…In 2004, Xiong et al [147] reported increased plasma leptin levels in mice following acute oral administration of sodium propionate. Enhanced expression of this anorexigenic hormone in human adipose tissue was also reported by Al-Lahham et al [148] in 2010. Both studies suggest an involvement of GPR41 in this process.…”
Section: Propionic Acidsupporting
confidence: 70%
“…Hence, the impact of PA on infl ammation could be linked to particular effects on obesity. Al-Lahham et al [148] observed that incubation of human adipose tissue with PA reduces the expression of resistin which is a pro-infl ammatory factor, the action of which is probably mediated by GPR43 on macrophages. Moreover, PA was reported to inhibit activated human lymphocyte proliferation in a concentrationdependent manner [158].…”
Section: Propionic Acidmentioning
confidence: 99%
“…However, shortchain fatty acids have been found to improve glycemic control, modulate nutrient trafficking and oxidation, modulate the expression level of several proteins/enzymes, that regulate energy balance including leptin, and may positively affect body weight control [54,66,67]. Given the involvement of leptin and adiponectin in glucose and energy metabolism, the negative association between butyric acid consumption and leptin/adiponectin ratio that has been detected in the current study, may reflect the beneficial metabolic effect of butyric acid.…”
Section: Discussionmentioning
confidence: 52%
“…One dietary fiber-derivative, propionic acid, was found to inhibit the expression level of resistin, a component of inflammation and insulin resistance [54]. The consumption of a healthy dietary pattern was associated with a significant reduction in resistin level in a large sample of apparently healthy women and the researchers suggested that the effect was mediated, partly, by cereal fiber consumption [35].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SCFA and BA receptors (i.e. GPR43 and FXR) are expressed in adipose tissue, and both SCFA and BA have been able to modulate fasting and β-adrenoceptor-mediated lipolysis in murine and human adipocytes [15,26]. indicating a possible role for BA and SCFA signaling in catecholamine-induced lipolysis.…”
Section: Discussionmentioning
confidence: 99%